Model Lean Manufacturing With The VSM Method to Reduce Waste In The Production Process Box Electrical Panel at PT.DMI - Kiswoyo, Danu; Muttaqin, Aan Zainal; Susanto, Doni (UNIPA PRESS, 2024)
DMI is a medium-sized company that produces electrical panel boxes. Make To Order (MTO) is a reference as the start of the production process. The production process includes plate cutting, bending, welding, grinding, powder coating and part-by-part assembly processes. Lean Manufacturing started in Japanese manufacturing, to eliminate all waste from the process while pursuing quality improvement in producing finished products. Value stream mapping is an important step in the lean transformation process before entering the waste elimination stage. which can lead to a decrease in the productivity of the company. One of the biggest problems was the lack of bending machines and not having our own powder coating machine.